Synthesis of 1, 2, 3-triazole 'click' analogues of thalidomide. Issue 40 (6th October 2016) - Ronnebaum, Jarrid M.; Luzzio, Frederick A.
Abstract: Click analogues of thalidomide were prepared from 3-azidoglutarimide and a diverse array of arylacetylenes and N -ethynyl/ N -propargyl phthalimide derivatives. The sequence necessitated a new and scalable synthesis of the key click intermediate 3-azidoglutarimide. The dipolar cycloaddition reactions between the azidoglutarimide and the alkynyl coupling partners utilized a copper sulfate/sodium ascorbate reagent system in aqueous tetrahydrofuran and were first explored using substituted arylalkynes. Along with the click analogues of thalidomide, the click counterparts of the teratogenic and antiangiogenic thalidomide analogue EM-12 were prepared. Graphical abstract: